ASSOCIATION OF LEPTOSPIRA SEROVARS WITH DIFFERENT CLINICAL CONDITIONS OF LEPTOSPIROSIS IN BUFFALOES - Govindanan, Balakrishnan (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study was undertaken to understand the involvement of different leptospiral serovars with different clinical conditions of leptospirosis among buffaloes. A total of 468 serum samples were collected from buffaloes with the history of abortion, repeat breeding, jaundice and haemorrhagic mastitis subjected to Microscopic agglutination test. Out of 468 serum samples, 329 (70.30 per cent) were found positive for 5 serovars namely pomona (28.27 per cent) hardjo (27.64 per cent), hebdomadis (23.00 per cent), australis (13.50 per cent) and ballum (7.59 per cent). Among the five serovars detected from buffaloes, reports are available only about serovar pomona which was found to be associated with abortion and jaundice. In the present study, it is observed that the influence of clinical signs over the seropositivity to leptospoirosis was statistically significant in buffaloes.